Cross-Layer Design of Coded Multicast for Wireless Random Access Networks - Rajawat, K.; Gatsis, N.; Seung-Jun Kim; Giannakis, G. B. (IEEE journal on selected areas in communications, 2011)
Joint optimization of network coding and Aloha-based medium access control (MAC) for multi-hop wireless networks is considered. The multicast throughput with a power consumption-related penalty is maximized subject to flow conservation and MAC achievable rate constraints to obtain the optimal transmission probabilities. The relevant optimization problem is inherently non-convex and hence difficult to solve even in a centralized manner. A successive convex approximation technique is employed to obtain a Karush-Kuhn-Tucker solution. A separable problem structure is obtained and the dual decomposition technique is adopted to develop a distributed solution. The algorithm is thus applicable to large networks, and amenable to online implementation. Numerical tests verify performance and complexity advantages of the proposed approach over existing designs. A network simulation with implementation of random linear network coding shows performance very close to the one theoretically designed.